F122. Non-lesional eating epilepsy with mesial temporal and inferior insular onset: A stereo-EEG study. (May 2018) - Aldosari, Mubarak; Joswig, Holger; Marti, Ana Suller; Parrent, Andrew; Mirsattari, Seyed M.
Abstract : Introduction: Reflex epilepsy is characterized by seizures that are triggered by internal or external stimuli. Based on the complexity of the trigger, the reflex epilepsies can be subdivided into simple and complex. Eating Epilepsy (EE) is a subtype of the complex reflex epilepsies and represents a heterogeneous electro-clinical syndrome. The body of literature on EE consists mostly of a few case series with variable medical and surgical outcomes. We present a case of non-lesional EE with excellent outcome from resective epilepsy surgery after an extensive pre-surgical investigation to identify of the seizure onset zone (SOZ). Methods: We retrospectively evaluated a case of drug-resistant eating-induced seizures referred for pre surgical assessment at London Health Sciences Centre Epilepsy Program, London, Canada. Patient's data was reviewed including clinical history, neurological exam, imaging (Brain MRI and FDG-PET), neuropsychology assessment, scalp video-EEG, Stereoelectroencephalography (SEEG) and the surgical management. Results: A 34-year-old gentleman has a 4-year history of seizures characterized by diffuse tingling sensation followed by loss of awareness with staring and right hand automatisms that lasted 1–2 min. 90% of his seizures were observed to be induced by eating at the beginning of a meal. His neuropsychological testing was essentially normal. Scalp video-EEG showed independent bilateral temporal spikes (R > L). Five eating-induced seizures were recorded immediately after initiation of eating with 2–3 Hz rhythmic activity over the right temporal region with perisylvian spreading. Brain MRI and PET studies were normal. Based on the electro-clinical data, the working hypothesis was right perisylvian onset of the seizures. The patient underwent intracranial recordings with stereo-EEG sampling the right temporal pole, amygdala, hippocampus, parietal operculum, temporal operculum and insula. Five seizures were captured induced by eating with stereotypical electrographic onset involving the right amygdala and hippocampus and inferior insula. Extra operative cortical stimulation (1–3.5 mA) elicited many prolonged after discharges in the same regions but they did not provoke clinical seizures. The patient thus underwent a right anterior temporal lobectomy and partial inferior insulectomy with decortication of the posterior short insular gyrus & the anterior and posterior gyri. Pathology revealed transcortical and hippocampal gliosis. He remained seizure-free (Engel 1) at his 8 months post-surgical follow-up. Conclusion: This case of a drug-resistant non-lesional EE illustrates the value of stereo-EEG in the presurgical work-up that led to seizure-freedom following combined right anterior temporal lobectomy and right inferior insula resection. In non-lesional cases of drug-resistant EE, the epileptogenic zone is likely wide and it requires stereo-EEG to determine the SOZ.